Biomechanical Effect of Orthodontic Treatment of Canine Retraction by Using Metallic Orthodontic Mini-Implant (OMI) Covered with Various Angles of Revolving Cap - Kuson Tuntiwong; Jui-Ting Hsu; Shih-Guang Yang; Jian-Hong Yu; Heng-Li Huang (Applied Bionics and Biomechanics)
Objective. This study evaluated the biomechanical effects of a metallic orthodontic mini-implant (OMI) covered with various types of angled revolving cap on the peri-OMI bone and the canine periodontal ligament (PDL) by finite element (FE) analyses. Materials and Methods. Three-dimensional FE models included comprised cortical bone and cancellous bone of the maxilla, and the OMIs were created. The forces (0.98 N) pulled in both the canine hook and the revolving cap, pulling towards each other in both directions as loading conditions. The upper surface of the maxilla was fixed as a boundary condition. Results. The bone stresses were increasing in the models by using OMI covered with a revolving cap as compared with that in the conventional model (in which only the OMI was placed). However, no obvious differences in bone stresses were observed among the models with various types of angled revolving cap. The minimum principal strain in the canine PDL was highest for condition 180T, followed by condition 180L. However, the maximum differences in the values between each experimental model and the conventional model were around 5%. Conclusion. This study showed no obvious effects in decreasing or increasing stress/strain in bone and PDL by using various types of angled revolving cap covered metallic mini-implant in orthodontic treatment of canine retraction.